COMPARATIVE ANALYSIS OF BATUPACK (SILICIFIED COAL) HANDLING STRATEGIES AT PT. BINA SARANA SUKSES, PT. MME SITE - Mulyadi, Riduan; Yusuf, Maulana; Setiawan, Budhi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The coal mining process at PT. Bina Sarana Sukses (PT. BSS) site PT.MME often encounters challenges in controlling coal quality. One of the main issue in the open-pit mine is the presence of batupack or silicified coal as impurities within nearly all coal seams, appearing both laterally as keybeds and as lens-shaped fragments. These impurities affect coal quality and hinder mining operations, while their hardness contributes to wear and damage o coal processing equipment, reducing operational efficiency. To address this, PT. BSS uses two strategies to separate batupack from coal: manual selective (handpicking) and bucket crusher excavators (BCE). A comparative analysis of these methods is required to evaluate technical feasibility and cost-effectiveness, to identify the most efficient approach to produce zero-contaminant coal and to set production targets. The study is conducted through a descriptive qualitative approach, which integrates preparation, scholarly review, compilation of primary and secondary information, and the stages of processing and analytical evaluation. The findings are expected to offer recommendations on the most effective and economical strategy for managing batupack impurities in coal mining operations.